The Impact of Neoadjuvant Hormone Therapy on Surgical and Oncological Outcomes for Patients With Prostate Cancer Before Radical Prostatectomy: A Systematic Review and Meta-Analysis - Zhang, Lijin; Zhao, Hu; Wu, Bin; Zha, Zhenlei; Yuan, Jun; Feng, Yejun (Frontiers in Oncology, 2021)
Objective: This systematic study aimed to assess and compare the comprehensive evidence regarding the impact of neoadjuvant hormone therapy (NHT) on surgical and oncological outcomes of patients with prostate cancer (PCa) before radical prostatectomy (RP). Methods: Literature searches were performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Using PubMed, Web of Science, Chinese National Knowledge Infrastructure, and Wanfang databases, we identified relevant studies published before July 2020. The pooled effect sizes were calculated in terms of the odds ratios (ORs)/ standard mean differences (SMDs) with 95% confidence intervals (CIs) using the fixed or random-effects model. Results: We identified 22 clinical trials (6 randomized and 16 cohort) including 20,199 patients with PCa. Our meta-analysis showed no signiﬁcant differences in body mass index (SMD=0.10, 95% CI: -0.08–0.29, p=0.274) and biopsy Gleason score (GS) (OR=1.33, 95% CI: 0.76–2.35 p=0.321) between the two groups. However, the NHT group had a higher mean age (SMD=0.19, 95% CI: 0.07–0.31, p=0.001), preoperative prostate-specific antigen (OR=0.47, 95% CI: 0.19–0.75, p=0.001), and clinic tumor stage (OR=2.24, 95% CI: 1.53–3.29, p<0.001). Compared to the RP group, the NHT group had lower positive surgical margins (PSMs) rate (OR=0.44, 95% CI: 0.29–0.67, p<0.001) and biochemical recurrence (BCR) rate (OR=0.47, 95% CI: 0.26–0.83, p=0.009). Between both groups, there were no signiﬁcant differences in estimated blood loss (SMD=-0.06, 95% CI: -0.24–0.13, p=0.556), operation time (SMD=0.20, 95% CI: -0.12–0.51, p=0.219), pathological tumor stage (OR=0.76, 95% CI: 0.54–1.06, p=0.104), specimen GS (OR=0.91, 95% CI: 0.49–1.68, p=0.756), and lymph node involvement (OR=0.76, 95% CI: 0.40–1.45, p=0.404). Conclusions: NHT prior to RP appeared to reduce the tumor stage, PSMs rate, and risk of BCR in patients with PCa. According to our data, NHT may be more suitable for older patients with higher tumor stage. Besides, NHT may not increase the surgical difficulty of RP.